PENGARUH TINGKAT PENDIDIKAN TERHADAP JUMLAH PENDUDUK MISKIN DI KABUPATEN SUMBAWA BARAT TAHUN 2015-2019 - K Kamaruddin; Nining Sudiyarti; Yuni Kurnilawan; Rosyidah Rachman (Pusat Riset dan Publikasi, 2020)
This study aims to determine the effect of the level of education on the number of poor people in West Sumbawa District. The variables in this study are the level of education as the independent variable and the number of poor people as the dependent variable. Data collection is obtained by documentation, observation, and literature study. Data were analyzed by calculating simple linear regression, statistical t test and coefficient of determination test (R2). The education level is divided into 3 levels, namely basic school, middle school and higher school. The results showed that the level of basic school had an effect on the number of poor people by 16.8%, the level of middle school had an effect on the number of poor people by 73.1%, The level of higher school had an effect on the number of poor people in West Sumbawa District by 48.3%.